IMPACT OF ACT OF THE REPUBLIC INDONESIA NUMBER 17 OF 2016 ON CHILDREN'S PROTECTION TOWARDS TEACHER PROFESSION - Satrul, Hairul Saleh (Journal of Islam and Science, 2018)
This study aims to (1) analyze the impact of implementing the Child Protection Act, 2) analyze the implementation of the Child Protection Act against teachers in disciplining students,(3) analyze efforts to protect the teaching profession in the formation of student discipline. This research uses a qualitative approach. Primary source of this research is the teacher. Data collection is carried out by means of observation, interviews and documentation. Data analysis using descriptive qualitative. Results of this study indicate that (1) Impact of the Child Protection Act has a positive impact for the development of students in schools, among others, avoid violence and the arbitrary actions of the teacher.(2)Teacher no longer uses the punishment aimed at the body and habitus in the formation of discipline. (3) Based on the juridical aspect, the addition of an explanation of differences in acts of violence by educating is one of the solutions in protecting the teacher so that there is no interpretation dualism. Based on social aspects, good cooperation between teachers and parents of students is based on an understanding of the role of each party. From the aspect of education, the principle of participation method is one that is used in forming the discipline of students in schools. Therefore, based on the findings that have been obtained it is recommended (1) Teachers must understand the essence of the Child Protection Act carefully. 2) It is time for the teacher to change the pattern of students from the old to the new patterns of students. (3) The communicative attitude is strengthened again so that there is good cooperation between the parties in the school so that the values being developed in the school are maintained.